Facility Utilization Study Fish Landing Base Dumai Riau Province - Ulva Uziel Hasiholan Limbong; Alit Hindri Yani; Jonny Zain (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
This study aimed to analyze the utilization study of Dumai Fish Landing Base facilities in Riau Province. This research was conducted in March 2023 at the Fish Landing Base (PPI) in Dumai City, Riau Province. The methods used in the study were surveys and interviews. The results showed that the fishing gear used by fishermen at PPI Dumai were gillnet, longline, sondong, and kurau net. The high percentage of utilization of dock facilities is about 545,45% and the port pool area is 139,98%, which means that the port pool area has exceeded highly utilized, while the utilization rate of the port pool depth is 87,5%, which means that it can still be utilized more optimally by fishermen. The utilization rate of the PPI Dumai auction building facility is 72,98%, which means that the auction building has exceeded being highly utilized